Diversity of cellulolytic bacteria from Macrotermes gilvus gut isolated from Indralaya peatland region, Indonesia - DWITA OKTIARNI; GETARI KASMIARTI; ERWIN NOFYAN; MIKSUSANTI MIKSUSANTI; HASANUDIN HASANUDIN; HERMANSYAH HERMANSYAH (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Oktiarni D, Kasmiarti G, Nofyan E, Miksusanti, Hasanudin, Hermansyah. 2021. Diversity of cellulolytic bacteria from Macrotermes gilvus gut isolated from Indralaya peatland region, Indonesia. Biodiversitas 23: 486-495. The termite Macrotermes gilvus Hagen from Tanjung Senai, Inderalaya peatland region, is classified as a high-level termite. Termites like eusocial insects break down cellulosic biomass into glucose by bacteria that produce cellulolytic enzymes in their gut. In the present study, new species of cellulolytic bacteria from Macrotermes gilvus Hagen gut were determined by biomolecular assay. Bacterial isolates were isolated and purified by using DNA kit and the optical density of DNA bacterial isolates was obtained by using spectrophotometer nanodrop. A total of 24 bacterial isolates were amplified using PCR to determine the fragment of 16S rRNA gene, performed using BLAST-N program and compared with NCBI database. Result from the sequences of 16S rRNA gene showed that the new species were identify as Enterobacter cloacae (isolates 1, 3, 6, 7, 10, 14, 19, 20, 25, 28, 39, 40, 44, 60, and 64), Klebsiella pneumoniae (isolates 24, 43, and 62), Klebsiella quasipneumoniae (isolates 29, 36, and 37), Klebsiella varicolla (isolate 52), Enterobacter roggenkampii (isolate 56) and Enterobacter asburiae (isolate 59).